Composite axial eyelid flap in the surgical management of orbitopalpebral neurofibromatosis - Parit Ladani; Hermann F Sailer; Megha Shah; Angad Shetye (Wolters Kluwer Medknow Publications, 2021)
Background: Orbitopalpebral neurofibroma is a progressive and debilitating disease with the potential of affecting the orbital, temporal and facial region. Lack of capsule and its infiltrative nature yields to difficulty in complete removal. Aims and Objectives: In this interventional case study, nine patients between the ages of 12-30 years diagnosed with orbitopalpebral neurofibromatosis underwent palpebral remodeling with composite axial eyelid flap for esthetic purpose and alleviation of visual impediment. Material and Methods: The clinical course for every individual was scored using Ptosis, Canthal involvement, and Oculopalpebral Diastasis (PCD) score on regular follow-ups. Results: For majority of the cases, an improvement was noted on the PCD scale. Conclusion: This series demonstrates that a tailored approach to each individual helps in attaining a balance between function and esthetic outcomes.